Salmonella cell rupture on a microfluidic chip using electroporation technique - S. Jaikla (2018)
Salmonella cell rupturing was performed on a microfluidic chip with electroporation technique. The gold electrode array for cell disruption was constructed on a glass substrate with the electrode gap and array gap of 100 μm and 50 μm, respectively. The PDMS microchannel was designed in order to concentrate the cells to flow between the array gaps. Teflon coating was applied to the electrodes to prevent heating and short-circuiting in the microchannel. The microchannel was treated with 1% BSA and then PBS to prevent cell adsorption on the PDMS. Bacterial cells were diluted in D-mannitol with an electric conductivity 53.4 μS/cm and strained with propidium iodide. Since propidium iodide is used as a DNA stain, we could use it to confirm the lysate of the cells. Spectrophotometer was used to detect cell lysate before and after the cell's passage to the microchannel. Both the operational voltage and the pulse duration were varied to achieve the effective cell rupture results. An operational DC voltage of 5V and 80 μs pulse duration, presented a high-percentage of bacterial cells to rupture. The disrupted cells percentage was 88% when compared to control. At these conditions, the generated electric field is higher than critical electric field strength that caused the cell membrane disruption and released of biological molecules. However, there is some amount of cells stuck in the channels during the operation. Thus, the bonding and treating of the microfluidic chip have to be further improved to increase the percentage of cell rupture. © 2011 IEEE.